Respuesta :
[tex]\bf z=\stackrel{r}{6}[cos(\stackrel{\theta }{315^o})+i~sin(\stackrel{\theta }{315^o})]\qquad
\begin{cases}
a=x=rcos(\theta )\\
b=y=rsin(\theta )\\
----------\\
a=6cos(315^o)\\
\qquad 6\left( \frac{\sqrt{2}}{2} \right)\\
\qquad 3\sqrt{2}\\
b=6sin(315^o)\\
\qquad 6\left( -\frac{\sqrt{2}}{2} \right)\\
\qquad -3\sqrt{2}
\end{cases}
\\\\\\
z=(~3\sqrt{2}~,~-3\sqrt{2}~)\implies z=3\sqrt{2}-3\sqrt{2}~i[/tex]
Answer:
The answer is:
[tex]\sqrt{6}(\cos 315\°+i\sin 315\°)=\sqrt{3}-i\sqrt{3}[/tex]
Step-by-step explanation:
The complex number is given as:
[tex]\sqrt{6}(\cos 315\°+i\sin 315\°)[/tex]
Now, we know that:
[tex]315\°=360\°-45\°[/tex]
Hence, we have:
[tex]\cos 315\°=\cos (360\°-45\°)\\\\i.e.\\\\\cos 315\°=\cos 45\°=\dfrac{1}{\sqrt{2}}[/tex]
( since, we have:
[tex]\cos (360\°-\theta)=\cos \theta[/tex] )
[tex]\sin 315\°=\sin (360\°-45\°)\\\\i.e.\\\\\sin 315\°=-\sin 45\°=-\dfrac{1}{\sqrt{2}}[/tex]
( since, we have:
[tex]\sin (360\°-\theta)=-\sin \theta[/tex] )
Now, the expression is simplified as follows:
[tex]\sqrt{6}(\cos 315\°+i\sin 315\°)=\sqrt{6}(\dfrac{1}{\sqrt{2}}-i\dfrac{1}{\sqrt{2}})[/tex]
i.e.
[tex]\sqrt{6}(\cos 315\°+i\sin 315\°)=\sqrt{6}\times \dfrac{1}{\sqrt{2}}-i\sqrt{6}\times \dfrac{1}{\sqrt{2}}[/tex]
i.e.
[tex]\sqrt{6}(\cos 315\°+i\sin 315\°)=\sqrt{3}-i\sqrt{3}[/tex]